2022
DOI: 10.3390/info13060289
|View full text |Cite
|
Sign up to set email alerts
|

Human Autonomy in the Era of Augmented Reality—A Roadmap for Future Work

Abstract: Augmented reality (AR) has found application in online games, social media, interior design, and other services since the success of the smartphone game Pokémon Go in 2016. With recent news on the metaverse and the AR cloud, the contexts in which the technology is used become more and more ubiquitous. This is problematic, since AR requires various different sensors gathering real-time, context-specific personal information about the users, causing more severe and new privacy threats compared to other technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Also the augmented reality is very closely related with human labor. The human using augmented reality solution will have possibility to increase its effectiveness knowledge and those solution will help works in many operations in business (Harborth, 2022). Using augmented reality can be a possibility to develop new interactive system which can increase the innovativeness of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Also the augmented reality is very closely related with human labor. The human using augmented reality solution will have possibility to increase its effectiveness knowledge and those solution will help works in many operations in business (Harborth, 2022). Using augmented reality can be a possibility to develop new interactive system which can increase the innovativeness of humans.…”
Section: Discussionmentioning
confidence: 99%
“…As Theodorou et al [37] note, "What is effectively transparent varies by who the observer is, and what their goals and obligations are." Lack of transparency hampers an individual's ability make informed decisions around systems in their environment [38], [39] and could lead to lack of trust in the systems [40]. Transparency with respect to mobile AR applications have been addressed in the context of permission settings, for example, whether to allow or decline object or face recognition [39].…”
Section: ) Transparencymentioning
confidence: 99%
“…Statistics have shown that the usage of AR has grown rapidly in the market since 2021 and will expand more henceforth [3]. In the past few years, AR applications were developed rapidly in fields such as entertainment (for promotional video, games, and social media), education (for teaching and learning), medical (such as MRI applications, jaw surgery [4]) and e-commerce (for shopping and home décor) (Puri et al, [4], Çöltekin et al, [5]).…”
Section: Introductionmentioning
confidence: 99%